Aid effectiveness: How is the L’Aquila food security initiative doing? - Benin, Samuel (International Food Policy Research Institute, 2014)
This paper uses case studies of Bangladesh, Ghana, Rwanda, and Senegal to assess the degree to which the L’Aquila Food Security Initiative (AFSI) has been implemented within the framework of managing for development results (MfDR) and to evaluate progress in various outcomes, including economic governance, agricultural growth, poverty, and food and nutrition security (FNS).